5-Bromo-2-hydroxybenzaidehyde (4-phenyl-1,3-thiazol-2-yl)hydrazone (vol E60, pg o889, 2004) - Genç, S; Dege, N; Yilmaz, I; Çukurovali, A; Dinçer, M (Int Union Crystallography, 2004)
[Abstract Not Available]